Perisplenic and Perinephric Abscess Secondary to Skin Infection: A Rare Case Report - Pradnya Diggikar; Bhavya S. Yammanuru; Sree V. Yekkaluru; Akhilesh Jagirdar (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
An abscess is a localized collection of pus within tissue spaces, typically secondary to bacterial infections, with the most common route of spread being hematogenous. Concurrent perisplenic and perinephric abscesses are rare complications, typically associated with significant diagnostic challenges. We report a case of a 57-year-old diabetic man presenting with abdominal discomfort and fever, later diagnosed with abscesses secondary to a skin infection caused by methicillin-sensitive Staphylococcus aureus (MSSA). Early intervention with percutaneous drainage and tailored antibiotics led to successful resolution. This report underscores the need for thorough diagnostic evaluation and an interdisciplinary approach to managing complex infections.